The learning motivation and experience of students in the International Baccalaureate stream of a Chinese government school - Chen, Yumei (2020)
This study explores the learning motivation and experiences of students in the International Baccalaureate stream of a Chinese government school. It investigates why they choose the International Baccalaureate (IB) instead of the domestic courses, and what differences, challenges, difficulties and successes the students found in learning on the International Baccalaureate programme.